Quality protein maize: QPM - Ignjatović-Micić Dragana (Genetika, 2008)
Quality protein maize (QPM) contains the opaque-2 gene along with numerous modifiers for kernel hardness. Therefore, QPM is maize with high nutritive value of endosperm protein, with substantially higher content of two essential amino acids - lysine and tryptophan, and with good agronomical performances. Although QPM was developed primarily for utilization in the regions where, because of poverty, maize is the main staple food, it has many advantages for production and consumption in other parts of the world, too. QPM can be used for production of conventional and new animal feed, as well as for human nurture. As the rate of animal weight gain is doubled with QPM and portion viability is better, a part of normal maize production could be available for other purposes, such as, for example, ethanol production. Thus, breeding QPM is set as a challenge to produce high quality protein maize with high yield and other important agronomical traits, especially with today's food and feed demands and significance of energy crisis.